2015
DOI: 10.11599/germs.2015.1069
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin minimum inhibitory concentrations and lethality in Staphylococcus aureus bacteremia

Abstract: Background After the dissemination of penicillin and oxacillin resistance in Staphylococcus aureus,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…We found only one isolate with reduced susceptibility with a minimum inhibitory concentration (MIC) =4 mg/L when tested with Etest and 2 mg/L when tested with microdilution. 2 , 3 Our results showed a tendency of higher lethality when higher MICs were present, even within the susceptible range, 3 as some previous studies have shown. 4 , 5 …”
supporting
confidence: 78%
See 1 more Smart Citation
“…We found only one isolate with reduced susceptibility with a minimum inhibitory concentration (MIC) =4 mg/L when tested with Etest and 2 mg/L when tested with microdilution. 2 , 3 Our results showed a tendency of higher lethality when higher MICs were present, even within the susceptible range, 3 as some previous studies have shown. 4 , 5 …”
supporting
confidence: 78%
“…We read the report by Phillips et al 1 with great interest and would like to discuss it in comparison with our previous published data on the subject. 2 , 3 …”
mentioning
confidence: 99%